FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP VOLUNTARY DISCLOSURE - Agustin, Tabita Dwi; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Voluntary disclosure is an important thing of the company to show the condition of the company to the investors. Nevertheless, some factors which have influence to the voluntary discovery still generate various kinds of model. In accordance with the problems, the purpose of this research is to find out whether profitability, liquidity, leverage, and firm size variables have influence to the voluntary disclosure on the financial statement of manufacturing companies which are listed in IDX in 2011-2012 periods. The samples are 74 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) and these companies have been selected by using purposive sampling. The audited financial statement data has been obtained from Indo-Exchange File. The multiple linear regressions are used as the statistic method that is used to determine some factors which have influence to the voluntary disclosure. The multicolinearity assumption test shows that there is no correlation among the independent variables so multicolinearity does not occur. The heteroscedasticity assumption test shows that the variants of constant disturbance probability distribution on the whole observation of independent variables do not occur, or in the other words heteroscedasticy does not occur in this research. The result of the research shows that liquidity and firm size variables significantly have been proven to have positive influence to the voluntary disclosure of the financial statement whereas the profitability variable and leverage significantly have not been proven to have positive influence to the voluntary disclosure of the financial statement of the manufacturing companies which are listed in Indonesia Stock Exchange (IDX).Keywords: Profitability, Liquidity, Leverage, Firm Size, Voluntary Disclosure.